Developing Infographic Teaching Materials for Introduction of Sapta Pesona-Based Character Value for Elementary School Students in the Bayah Dome Geopark Area, Lebak Regency - Hanif, Muhammad; Khosihan, Aan; Setiawan, Budi; Haryani, Puput; Firdaus, Aryanti Putri (Universitas Sebelas Maret, 2023)
This research targets geopark's two potentials in education and tourism by introducing and inculcating the Sapta Pesona character values using infographic teaching materials. Infographic book media is deemed a medium appropriate to the concrete thinking stages of elementary school students, which displays information visualization in an interesting and structured way. Therefore, this study intends to develop an infographic book introducing geopark and instilling Sapta Pesona character values for elementary school students, implemented in the local content curriculum in several elementary schools closest to the Bayah Dome Geopark area. Through research and development (R&D) methods with three main stages: (1) preliminary study stage, (2) design and development stage, and (3) product testing stage, this research produced an infographic book product to recognize the potential of geoparks and their character values that can be used as supplementary media for elementary school local content. The results of this study are expected to be an alternative introduction to the potential of geopark as a medium of learning and instilling character values targeting elementary school-age students. In addition, this research is a follow-up to the Lebak Regency MoU with UPI Serang Campus to optimize UPI's role in contributing to the sustainable development goals of potential areas in Indonesia. The development of Sapta Pesona-based infographic teaching materials in the Bayah Dome Geopark area, Lebak Regency, could be carried out properly; likewise, the teaching materials created could be adequately implemented. Many students in the Bayah Dome Geopark area of Lebak Regency were interested in teaching materials with pictures in infographics, where not-too-much reading and visualized through pictures made this ‘Asyiknya Bayahku' teaching material book more attractive and liked by students in elementary schools. Moreover, the teacher's enthusiasm for new teaching materials regarding independent curriculum learning has brought this research to further development due to much help from teachers waiting for these books and materials to be implemented in schools. Furthermore, the implementation of this book also positively impacted the application of character values in schools where this teaching material was implemented.